Parenting Challenges of Child Rearing in a Changing Society - Ali Samadi, Sayyed (IntechOpen, 2022)
Parenting is a lifelong task and parents are always remaining as a parent. Parenting in the present situation faces many challenges which need to be reviewed and understood with profuse equanimity and alacrity. This book tries to consider the process of parenting in different conditions such as during COVID-19 lockdown, in the refugee camps, and in different cultural structures and economic conditions. Situations that families face due to changing conditions such as global changes which cause lifestyles, immigration patterns, social conflicts, and raising children with developmental disabilities have been discussed. Topics such as professional concern with child care and education, gender roles and caregiving, and father's involvement in parenting, have been covered in different chapters of the book.